Resolvin E1 in Follicular Fluid Acts as a Potential Biomarker and Improves Oocyte Developmental Competence by Optimizing Cumulus Cells - Zhang, Yijing; Zhu, Zhongyi; Li, He; Zhu, Mingjiang; Peng, Xiandong; Xin, Aijie; Qu, Ronggui; He, Wen; Fu, Jing; Sun, Xiaoxi (Frontiers in Endocrinology, 2020)
Metabolic profile of follicular fluid (FF) has been investigated to look for biomarkers for oocyte quality. Resolvin E1 (RvE1), a potent pro-resolving mediator, was reported to have protective action in cell function. The study aimed to examine the predictive value of RvE1 for oocyte quality and to explore the cellular mechanism of RvE1 in improving oocyte competence. Metabolic profiles of 80 FF samples showed a higher level of RvE1 in group A (blastocysts scored ≥ B3BC and B3CB according to Gardner's blastocyst scoring system, N = 36) than that of group B (blastocysts scored < B3BC and B3CB, N = 44, P = 0.0018). The receiver operating characteristic (ROC) curve analysis showed that RvE1 level in FF below 8.96 pg/ml (AUC:0.75; 95%CI: 0.64–0.86; P = 0.00012) could predict poor oocyte quality with specificity of 97.22%, suggesting RvE1 as a potential biomarker to exclude inferior oocytes. Besides, the level of RvE1 was found to be significantly lower in FF than in serum (57.49 to 17.62 pg/ml; P=.0037) and was gradually accumulated in the culture medium of cumulus cells (CCs) during cell culture, which indicated that RvE1 came from both blood exudates and local secretion. The in vitro experiment revealed thecellular mechanism of RvE1 in improvingoocyte qualityby decreasing the cumulus cellapoptotic rate and increasing cell viability and proliferation. It is the first time thatthe role of RvE1 in reproduction is explored. In conclusion, RvE1 is valuable as a potential exclusive biomarker for oocyte selection andplays a role in improving oocyte quality.